(3eMGSHI GdJcGdja (B/s - (3GdLHGdj, eMehO Ydjs; (3GdSGeQGFj, bUjs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2000)
(3WHjYI h CgOGa h JYQja eMGSHI GdJcGdja, EYOGO bhGFe GdJcGdja MSH JHhjH YfGUQ GdJcGdja, GdQbGHI h GdeMGSHI Yf JcdaI YfUQ GdehGOh Yf YfUQ GdYed, GdJcGdja ZjQ GdeHGTQI h bhGFe GdJcGdja , fXGe GdbhGFe GdGfJGLjI h fXGe GdehGMd GdGfJGLjIs
Keywords: (3GdeMGSHIs; (3eMGSHI GdJcGdjas